2020
DOI: 10.1109/access.2020.2974320
|View full text |Cite
|
Sign up to set email alerts
|

Connectivity-Based Localization in Ultra-Dense Networks: CRLB, Theoretical Variance, and MLE

Abstract: Performance analysis of connectivity-based geolocation in ultra-dense networks (UDNs) is a very important task. Although several performance analyses have been presented for range-free localization, determining the best achievable positioning accuracy of range-free localization remains an open problem. In this paper, we first derive the Cramer-Rao lower bound (CRLB) for the performance evaluation of range-free localization. All the current performance analyses in the literature for range-free localization are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Many localization methods are presented in the literature [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. There are two ways to locate a sensor in WSNs: (1) range-based and (2) range-free methods.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many localization methods are presented in the literature [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. There are two ways to locate a sensor in WSNs: (1) range-based and (2) range-free methods.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with those on range-based techniques, relatively fewer studies [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ] have been reported for range-free location techniques. Among range-free methods, Centroid-based localization (CL) is the most famous; it functions by determining the BN’s position as the centroid of RNs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This lower bound can easily help select the best estimator for a given problem in hand based on the minimum variance it can attain. On the other language, the bound tells how best one can achieve during a given estimation problem (Alslaimy and Smith, 2019;Huang et al, 2020;Hung et al, 2020;Kay, 1993;Khorasani et al, 2020;Li et al, 2021;Mao et al, 2020;Tian et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…This lower bound can easily help select the best estimator for a given problem in hand based on the minimum variance it can attain. On the other language, the bound tells how best one can achieve during a given estimation problem (Alslaimy and Smith 2019, Huang et al 2020, Hung et al 2020, Kay 1993, Khorasani et al 2020, Li et al 2021, Mao et al 2020, Tian et al 2020.…”
Section: Introductionmentioning
confidence: 99%